A companion to social geography - Del Casino, Vincent J.; Del Casino, Vincent J. (Chichester, West Sussex ; Malden, MA. : Wiley-Blackwell, 2011)
This volume traces the complexity of social geography in both its historical and present contexts, whilst challenging readers to reflect critically on the tensions that run through social geographic thought. Organized to provide a new set of conceptual lenses through which social geographies can be discussedPresents an original intervention into the debates about social geographyHighlights the importance of social geography within the broader field of geography.
Front Matter -- Introduction / Vincent J Del Casino, Mary E Thomas, Paul Cloke, Ruth Panelli -- Ontological Tensions in/of Society and Space. Part Introduction / Paul Cloke -- Difference / Sarah de Leeuw, Audrey Kobayashi, Emilie Cameron -- Identification / Katharine McKinnon -- Social Natures / Katharine Meehan, Jennifer L Rice -- Economie$ / Geoff Mann -- Community / Marcia England -- Belonging / Caroline Nagel -- Thinking and Doing Social Geographies. Part Introduction / Vincent J Del Casino -- Knowing/Doing / Richard Howitt -- Framing the Field / Joanne Sharp, Lorraine Dowler -- On the Ground / Bettina van Hoven, Louise Meijering -- Leaving the Field / Carolyn Gallaher -- The Worldly Work of Writing Social Geography / Lieba Faier -- Participatory Praxis and Social Justice / C Kinpaisby-Hill -- Using Social Geography / Sarah Johnsen -- Matters and Meanings. Part Introduction / Mary E Thomas -- Molecular Life / Gail Davies -- Psychic Life / Hester Parr, Joyce Davidson -- Sexual Life / Gavin Brown, Kath Browne, Jason Lim -- Emotional Life / Deborah Thien -- Affective Life / Keith Woodward -- Embodied Life / Isabel Dyck -- Discursive Life / Chris Philo -- Spiritual Life / Julian Holloway -- Virtual Life / Mike Crang -- Power and Politics. Part Introduction / Ruth Panelli -- Geopolitics / Nancy Hiemstra, Alison Mountz -- The Geographies of Marginalization / Dan Trudeau, Chris McMorran -- Care and Caring / David Conradson -- The Challenges of and from Indigenous Geographies / Brad Coombes, Nicole Gombay, Jay T Johnson, Wendy S Shaw -- Transnational Geographies and Human Rights / Amy Ross -- Resistance(s) and Collective Social Action / Paul Chatterton, Nik Heynen -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Human geography; Environmental Studies; Social Science; SOCIAL SCIENCE -- Human Geography; Human geography; Kulturgeografi; Electronic books